Using Simulation to Evaluate Discharge Communication: The Relationship between Realism, Presence, and Student Learning Outcomes - MacLean, Sharon (Curtin University, 2020)
Discharge communication skills training can have a positive impact on patient outcomes. To assist students transitioning into clinical practice simulation-based education is employed in nursing to teach communication skills. In this study, a student-centred conceptual model of simulation was developed and tested. This research highlighted that simulation-based education is beneficial in developing undergraduate nurse’s communication skills.